P939Identifying predictive electrocardiographic features for ventricular fibrillation during acute myocardial infarction in an ovine model. (18th June 2020) - Pius, C; Niort, B; Pinali, C; Dibb, K; Trafford, A
Abstract: Funding Acknowledgements: British Heart Foundation Introduction: Myocardial infarction (MI) is a leading cause of mortality with complications such as left ventricular dysfunction and arrhythmias. Despite the well characterized clinical characteristics of MI, little is known about the cellular remodeling that occurs. Altered calcium (Ca2+) handling in disease can give rise to Ca2+ waves resulting in a transient inward current via the Na+- Ca2+ exchanger. Under certain conditions this causes membrane depolarization and potentially triggered arrhythmias. Since abnormal intracellular Ca2+ handling leads to both dysfunction and arrhythmias, an ovine MI model was established to simultaneously investigate cellular and in vivo alterations that occur post-MI. Methods: Young female sheep (∼18 months) were randomly allocated as control or for MI induction surgery. A minimally invasive technique was used to create the infarct by occluding the left anterior descending coronary artery. Electrocardiograms (ECG) were recorded at intervals. At 8 weeks, ventricular cells were isolated from the infarct border zone (BZ) and loaded with a Ca2+ indicator to study the systolic calcium transient, calcium sparks and occurrence of calcium waves. Statistical significance was taken as p < 0.05, determined using t-test, Friedman's test and Fisher's exact test. N= animals, n = cells. Results: The majority of animals had ventricular rhythm abnormalities at around 30 minutes post coronary occlusion (N = 8/11). However, the severity of the ventricular arrhythmias was variable between animals. Preliminary data suggests the animals which had ventricular fibrillation (VF) (N = 3) had ECG evidence of QT interval prolongation at 30 minutes post occlusion (618 ± 42ms), reperfusion (516 ± 46ms) and at the end of surgery (625 ± 109ms) compared to baseline (324 ± 6ms). Animals without VF (N = 3) demonstrated QT prolongation on reperfusion (562 ± 44ms) compared to baseline (348 ± 31ms). In animals with VF, the T peak-T end interval also increased at 30 minutes post occlusion (115 ± 13ms) compared to baseline (35 ± 5ms). Overall, the QT interval remained unchanged at 8 weeks compared to baseline along with the QRS duration, PR and RR interval with the exception of the ST segment at week 1 which was elevated by 0.05 ± 0.01mV (N = 7). On a cellular level, preliminary data indicated increased propensity for Ca2+ waves in MI BZ compared to control cells (37% vs 49%) and larger amplitude Ca2+ sparks (control = 1.65 ± 0.03, MI BZ 2.13 ± 0.11. N= 38 control, 5 MI BZ) in the BZ compared to control. Conclusion: The alteration in the QT and T peak-T end interval at 30 minutes post occlusion is reflective of alterations in ventricular repolarization and may be related to the incidence of more severe arrhythmias during MI. The increased propensity for Ca2+ waves and larger amplitude Ca2+ sparks in BZ suggests Ca2+ handling remodeling. Given the proarrythmic characteristics of aberrant calcium release, this may explain complications seen post-MI.